Gershom Scholem’s First Lectures on Hasidism - Meir, Jonatan (Jewish Thought, 2022)
Compared to his other fields of research, Gershom Scholem’s studies of Hasidism were quite limited. In the major research plans which he developed in the 1920s and ‘30s – for example in his detailed letter to H.N. Bialik or his early plans for the Institute for Kabbalah at the Schocken Library — he makes no mention of this field of research. Still, he continually and systematically published on Hasidism over the years. Scholem’s scattered articles on Hasidism were collected in recent years by David Assaf and Esther Liebes in the anthology “The Latest Phase,” with updates and additions; this collection gives us a full picture of Scholem’s contribution to the field. Much scholarship has also been dedicated to the controversy between Scholem and Martin Buber over Hasidism, or to be more precise, to the complex relationship between the two over the years. Some have come to read Scholem’s studies of Hasidism from this vantage point alone. However, Scholem’s deep interest in Hasidism was expressed in other ways: in his large collection of books which includes many Hasidic works with his handwritten marginal notes; in his drafts and notes for articles which were never completed; and in lectures on the subject which he gave over the years. This material remains hidden in the Gershom Scholem Archive and has never been collected. Of exceptional importance is a manuscript of a complete book on Hasidism in English, composed towards the end of 1948, which provided the basis of the lectures that Scholem gave in the United States in March 1949. This book, written in the context of his complicated relationship with Salman Z. Schocken, was also the basis of many studies which Scholem published years late, and he continually updated it over many years. Our interest here is in another hidden text: a series of early lectures on Hasidism which Scholem gave in Hebrew in 1945. This series – printed here for the first time – raises several fundamental questions about Scholem’s studies of Hasidism and their relationship to Buber’s projects, and shows with great clarity the manner in which Scholem wanted to portray Hasidism.